Development of Interactive Multimedia Based on STEM Wave Material for High School Students - Anissa Arianti; Leni Marlina; Ida Sriyanti (Universitas Lambung Mangkurat, 2022)
This research analyses the results of expert validation of interactive multimedia development based on STEM wave material for high school students. This development research used the Alessi and Trollip model, which includes the planning, design, and development stages. Validation is one of the stages in product development. Conducted by one material expert and one media expert. The validation results were analyzed by converting quantitative data into qualitative data with five scales. The results of material validation include content feasibility with 17 indicators obtained an average value of 0.823, presentation feasibility with nine indicators obtained an average value of 0.826, and language assessment with ten indicators obtained an average value of 0.825. It means each indicator belongs to the very high category The results of media validation which include graphics with seven indicators obtained an average value of 0.892, colouring with three indicators obtained an average value of 0.916, interactivity with 11 indicators obtained an average value of 0.909, and sound with three indicators obtained an average value of 0.833, which is each indicator included in the very high category. Experts argue that interactive multimedia based on STEM wave material for high school students is considered valid and worth testing.